Kontruksi Makna dan Perilaku Budaya Ngopi di Starbucks - Hagi Farizi; Mayasari Kurniawan; Rastri Kusumaningrum (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research explores the construction of meaning and the cultural behaviour of drinking Coffee in Starbucks Coffee. In this article I will discuss how someone drinks coffee in Starbucks, or how their behaviour influences their reasoning to drink coffee in Starbucks. The research location used for this research is Starbuckks DT Galuhmas Karawang. The subject of this research is the customers of Starbucks DT Galuhmas Karawang. The data gathering method utilized in this research is using interview, non-participant observation, ltierature review, and documentative study. This research utilizes the phenomenology theory developed by Alfred Schuzts. The research methodology used is qualitative with the descriptive qualitative approach intended to explain the meaning and cultural behaviour that influence the purpose of customers to come and drink coffee in Starbucks. The result of this research is the view of a customer to give meaning in drinking coffee in starbucks as a platform of socialization and lifestyle.